Inequality of income and wealth in the long run: A Kaldorian perspective - Soon Ryoo (University of Massachusetts, Department of Economics, 2015)
The paper examines the determinants of income and wealth inequality in a Kaldorian model where the profit share adjusts to clear the goods market and the long-run output-capital ratio is constant. The approach is radically different from both the mainstream approach that stresses properties of production function and the Kaleckian approach that emphasizes the long-run adjustment of utilization. The Kaldorian model is used to identify several developments that may have caused increasing inequality in income and wealth since the early 1980s, including the shift of the power relation in corporate firms in favor of top managerial pay, the decline in the retention rate, increasing share buybacks, rising indebtedness of lower-income households, and the stock market boom in the 1990s. In contrast to Piketty's explanation, the decline in the natural rate of growth reduces inequality of income and wealth in this Kaldorian framework.
Keywords: E12; E21; E25; E44; 330; income and wealth distribution; managerial pay; financialization; stock-flow consistency